Synergistic Effects of Climate Change and Alien Fish Invasions in Freshwater Ecosystems: A Review - Antonella Carosi; Francesca Lorenzoni; Massimo Lorenzoni (Fishes, 2023)
The interaction between climate warming and alien fish invasions could have severe consequences in inland waters, which represent isolated environments with high biodiversity richness. Due to the current climatic trend, increasing water temperatures and salinization, shorter ice cover period, and altered flow regimes are predicted for these environments. The aim of this review is to offer a comprehensive analysis at a global scale of the recent studies available in the literature, focused on the responses of invasive freshwater fish to the effects of climate change in both lotic and lentic environments. To achieve this purpose, we selected 34 relevant papers, using the Scopus and Google Scholar database. New alien species establishment, distribution range expansion of species already introduced, and exacerbating impacts on freshwater ecosystems and the native fish communities they host were included in the topics covered by the analyzed papers. Despite the uncertainties related to the unpredictability with which the effects of global warming will occur, the findings of the selected studies served as a support to evaluate conservation and management implications, with particular reference to possible mitigation strategies.